Preparation method of hollow Prussian blue positive electrode material

Hollow Prussian blue was synthesized under additive-free conditions by anion exchange method, combined with the traditional bimetal source coprecipitation method and the double iron source method, the problem of uneven composition of existing materials was solved, and the preparation of high-quality materials and excellent electrochemical properties were achieved.

CN119612552APending Publication Date: 2025-03-14ZHEJIANG SHANGAO NEW ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411933192.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing hollow Prussian blue materials need to be added to the synthesis process, resulting in uneven composition and affecting its electrochemical properties.

Method used

Hollow Prussian blue was synthesized under the condition of no additives by anion exchange method, ferrous cobalt cyanide was prepared by the traditional bimetal source coprecipitation method, and hollow Prussian blue was prepared by the double iron source method, and then it was soaked in a special impregnation solution for modification.

Benefits of technology

The synthesis of high-quality hollow Prussian blue under additive-free conditions has been achieved, which improves the electrochemical performance of the material, including conductivity, thermal stability and mechanical strength, and significantly improves its cycling performance in sodium ion batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of a hollow Prussian blue positive electrode material, which takes Fe-Co Prussian blue as a raw material, adopts an anion exchange method to prepare Fe-Fe Prussian blue with a hollow structure, optimizes the transmission path of electrons and ions in the Prussian blue, reduces the number of defect sites and interstitial water content in the Prussian blue structure, and improves the performance of the hollow Prussian blue positive electrode material. The specific discharge capacity and the electrochemical cycle performance of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of novel sodium ion battery positive electrode materials, and specifically relates to a method for preparing a hollow Prussian blue positive electrode material. Background Art

[0002] Prussian blue analogs (PBAs) have high theoretical specific capacity and open three-dimensional framework structure and are considered to be one of the most promising sodium ion cathode materials.

[0003] Patent CN115367772B discloses a method for preparing a Prussian blue cathode material. The high-speed shearing method is used to replace the traditional magnetic stirring or mechanical stirring method, so that the entire reaction system in the coprecipitation process is close to the ideal reaction state to the greatest extent, and each ion is evenly dispersed in the solution and complexed with each other at the same probability; at the same time, the present invention controls the temperature of the coprecipitation and aging process, and regulates the grain nucleation growth process to obtain a Prussian blue cathode material with high crystallinity, low defects, low water content and high sodium content.

[0004] Patent CN117326571A discloses a method for improving the crystallinity of Prussian blue, Prussian blue, positive electrode material and battery. The method for improving the crystallinity of Prussian blue comprises the following steps: mixing low-crystallinity Prussian blue and its analogs, an aqueous solution of an alcohol compound, hexacyanoferrate (II) and a reducing substance to obtain a reaction solution; reacting the reaction solution at a temperature of 40-80°C to obtain a solid precipitate; washing and drying the prepared solid precipitate to obtain a high-crystallinity Prussian blue.

[0005] However, although the modification of Prussian blue has improved its electrochemical cycle performance, there are still a large number of defects in the material, which seriously restricts its electrochemical performance. The hollow Prussian blue synthesized by the self-template method is currently prepared by the cation exchange method. The synthesis process requires the addition of etchants and surfactants, and metal cation doping is prone to occur during the preparation process, resulting in uneven composition of the final material, affecting its electrochemical performance. The anion exchange method for preparing hollow Prussian blue as a positive electrode material for sodium ion batteries has attracted attention. Summary of the invention

[0006] The invention aims to provide a method for synthesizing hollow Prussian blue by anion exchange, and the hollow Prussian blue is synthesized under the condition of no additives.

[0007] The technical solution of the present invention is: a method for preparing a hollow Prussian blue positive electrode material, comprising the following steps: A. Synthesis of ferrocobalt cyanide: ferrocobalt cyanide was prepared by the traditional double metal source coprecipitation method. First, FeSO4·7H2O and K3Co(CN)6·10H2O were dissolved in appropriate amounts of deionized water according to a certain molar ratio, marked as solution A and solution B. Then, solution B was dropped into solution A under argon gas protection. The free Fe in the solution 2+ Will be with Co(CN) 3- The combination undergoes a coprecipitation reaction, and finally a white precipitate is obtained. The precipitate is collected after aging, washed with a detergent, and finally dried in a vacuum oven to obtain a sample of ferrocobalt cyanide.

[0008] B. Synthesis of hollow Prussian blue: Hollow Prussian blue was prepared by the double iron source method. First, an appropriate amount of Na4Fe(CN)6·10H2O was dissolved in a certain amount of deionized water to form solution A. Then, an appropriate amount of ferrous cobalt cyanide was weighed and placed in a certain amount of deionized water. Suspension B was formed by magnetic stirring. Under specific argon gas protection conditions, solution A was slowly dripped into solution B through a peristaltic pump. At this time, Fe(CN) in the solution 4- Fe 2+ A coprecipitation reaction occurs to form Prussian blue, and the white suspension gradually turns into a blue suspension. After the mixed solution is left for a period of time, it is centrifuged to obtain a dark blue precipitate, which is washed with a detergent, dried under vacuum, and dehydrated to obtain a sample hollow Prussian blue.

[0009] C: Soak the dehydrated hollow Prussian blue in the impregnation solution, filter, and vacuum dry to obtain the modified hollow Prussian blue.

[0010] D. Assemble the battery and test its discharge capacity and cycle performance at a current density of 1C.

[0011] As a preferred technical solution of the present invention, in step A, the molar ratio of FeSO4·7H2O to K3Co(CN)6·10H2O is 0.2-0.4:0.1-0.3.

[0012] As a preferred technical solution of the present invention, in step A, the amount of deionized water added is 80-120 mL.

[0013] As a preferred technical solution of the present invention, in step A, the precipitation aging time is 10-14h.

[0014] As a preferred technical solution of the present invention, in step A, the detergent is one or both of deionized water and anhydrous ethanol.

[0015] As a preferred technical solution of the present invention, in step A, the washing times are 2-5 times.

[0016] As a preferred technical solution of the present invention, in step A, the precipitate is dried in a vacuum oven at 100-200° C. for 10-20 hours.

[0017] As a preferred technical solution of the present invention, in step A, the molar ratio of Na4Fe(CN)6·10H2O to ferrous cobalt cyanide is 0.5-0.7:0.05-0.15.

[0018] As a preferred technical solution of the present invention, in step B, the amount of deionized water added to solution A is 400-800 mL, and the amount of deionized water added to solution B is 80-200 mL.

[0019] As a preferred technical solution of the present invention, in step B, the suspension is placed for 12-36 hours.

[0020] As a preferred technical solution of the present invention, in step B, the detergent is one or both of deionized water and anhydrous ethanol.

[0021] As a preferred technical solution of the present invention, in step B, the preparation method of the impregnation solution is: K1: According to weight, 0.12-0.24 parts of 2-methyl-3-mercaptofuran, 200-300 parts of acetonitrile, 0.1-0.2 parts of allylphenyl sulfoxide, 0.03-0.06 parts of triethylamine, stirred at 70-80°C for 60-100 minutes, K2: Add 0.008-0.03 parts of 1-vinyl-3-methylimidazolium acetate CAS: 1416358-75-2, stir at 70-80°C for 30-60 minutes, and cool to obtain an ionic liquid impregnation solution containing furan, phenyl sulfoxide and imidazole acetate.

[0022] As a preferred technical solution of the present invention, in step B, the dehydrated hollow Prussian blue is immersed in the impregnation solution for 8-14 hours, filtered and then vacuum dried at 70-80° C. for 10-15 hours.

[0023] Reaction mechanism: 1. Addition of 2-methyl-3-mercaptofuran and allylphenyl sulfoxide: This reaction is a typical thiol-ene click chemistry reaction. In this process, the thiol group (-SH) in 2-methyl-3-mercaptofuran attacks the carbon-carbon double bond in allylphenyl sulfoxide. This reaction forms a new CS bond through a stepwise addition-elimination process to obtain an intermediate.

[0024] 2. Addition of 2-methyl-3-mercaptofuran and 1-vinyl-3-methylimidazole acetate: 2-Methyl-3-mercaptofuran is used as the thiol component, and 1-vinyl-3-methylimidazolium acetate is used as the component with a carbon-carbon double bond. The thiol group attacks the double bond and forms a stable product through a stepwise addition-elimination mechanism. In this process, the imidazole ring in 1-vinyl-3-methylimidazolium acetate may interact with the newly formed thioether structure through the π electrons on the ring, further enhancing the stability and reaction selectivity of the product.

[0025] Technical effect: 1. Improvement of electrical conductivity: The ionic liquid components in the impregnation solution, such as imidazole acetate, can effectively improve the overall conductivity of the battery due to its high ionic conductivity. This not only promotes more efficient charge transfer, but also reduces the internal resistance of the battery during operation.

[0026] Organic compounds such as furan and phenyl sulfoxide help smooth the electrode surface by filling microscopic defects on the electrode surface, thereby reducing the interfacial impedance between the electrode and the electrolyte. This improved interfacial contact is conducive to more efficient charge transfer and reduced side reactions on the electrode surface.

[0027] 2. Improvement of thermal stability: Organic compounds in the impregnation solution, such as phenyl sulfoxide and imidazole acetate, have a certain thermal stability, which helps to improve the performance retention of the battery in high temperature environments.

[0028] 3. Strengthening of mechanical strength: By filling the vacancy defects on the electrode surface, the impregnation solution enhances the structural integrity of the electrode material, thereby improving the material's mechanical strength and ability to resist volume expansion, which is particularly important during long-term charge and discharge cycles. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with specific implementation modes.

[0030] Embodiment 1, A method for preparing a hollow Prussian blue positive electrode material comprises the following steps: A. Synthesis of ferrocyanide: ferrocyanide was prepared by the conventional double metal source coprecipitation method. First, 45.6 g FeSO4·7H2O and 66.5 g K3Co(CN)6·10H2O were dissolved in 100 ml deionized water, marked as solution A and solution B, respectively. Then, under argon gas protection, solution B was dropped into solution A. The free Fe in the solution was 2+ Will be with Co(CN) 3-The coprecipitation reaction occurred and a white precipitate was finally obtained. The precipitate was collected after aging for 12 hours, washed three times by centrifugation with deionized water and anhydrous ethanol respectively, and finally dried in a vacuum oven at 120 °C for 12 hours to obtain the sample of cobalt ferrocyanide.

[0031] B. Synthesis of hollow Prussian blue: Hollow Prussian blue was prepared by the double iron source method. First, 290g Na4Fe(CN)6·10H2O was dissolved in 500ml deionized water to form solution A. 21g ferrocyanide was weighed and placed in 100ml deionized water, and a suspension B was formed by magnetic stirring. Then, under specific argon gas protection conditions, solution A was slowly dripped into solution B through a peristaltic pump. At this time, the Fe(CN) in the solution 4- Fe 2+ A coprecipitation reaction occurred to form Prussian blue, and the white suspension gradually turned into a blue suspension. After the final mixed solution was placed for 24 hours, a dark blue precipitate was obtained by centrifugation, which was washed three times with deionized water and anhydrous ethanol respectively, and finally dried under vacuum at 0.3 mTorr and 120 °C for 12 hours to obtain a hollow Prussian blue sample.

[0032] C. Soak the dehydrated hollow Prussian blue in the impregnation solution for 12 hours, filter and dry under vacuum at 75° C. for 12 hours to obtain the modified hollow Prussian blue. The preparation method of the impregnation solution is: K1: According to weight, 20.55 g of 2-methyl-3-mercaptofuran, 250 mL of acetonitrile, 25 g of allylphenylene glycol, and 4.04 g of triethylamine were stirred at 75° C. for 80 minutes.

[0033] K2: Add 25.5 g of 1-vinyl-3-methylimidazolium acetate CAS: 1416358-75-2, stir at 75°C for 50 minutes, and cool to obtain an ionic liquid impregnation solution containing furan, phenyl sulfoxide and imidazole acetate.

[0034] D. The battery was assembled and tested, and its discharge specific capacity at a current density of 1C was 138.6 mAh / g, and the capacity retention rate after 100 cycles was 96%.

[0035] Embodiment 2, A method for preparing a hollow Prussian blue positive electrode material comprises the following steps: A. Synthesis of ferrous cobalt cyanide: Ferrous cobalt cyanide was prepared by the traditional bimetallic source co-precipitation method. First, 30.4 g FeSO4·7H2O and 33.2 g K3Co(CN)6·10H2O were dissolved in 80 ml deionized water, marked as solution A and solution B, respectively. Then, under argon gas protection, solution B was dropped into solution A to obtain a white precipitate. The precipitate was aged for 10 h and then collected. It was washed twice by centrifugation with deionized water and anhydrous ethanol, respectively, and finally dried in a vacuum oven at 100 °C for 10 h to obtain a sample of ferrous cobalt cyanide.

[0036] B. Synthesis of hollow Prussian blue: Hollow Prussian blue was prepared by the double iron source method. First, 242 g Na4Fe(CN)6·10H2O was dissolved in 400 ml deionized water to form solution A. 11 g ferrocyanide was weighed and placed in 80 ml deionized water. Suspension B was formed by magnetic stirring. Then, under specific argon gas protection conditions, solution A was slowly dripped into solution B through a peristaltic pump. At this time, Fe(CN) in the solution 4- Fe 2+ A coprecipitation reaction occurred to form Prussian blue, and the white suspension gradually turned into a blue suspension. After the final mixed solution was placed for 12 hours, it was centrifuged to obtain a dark blue precipitate, which was washed twice with deionized water and anhydrous ethanol respectively, and finally dried under vacuum at 0.1 mTorr and 100 °C for 10 hours to obtain a hollow Prussian blue sample.

[0037] C. Soak the dehydrated hollow Prussian blue in the impregnation solution for 8 hours, filter and dry under vacuum at 70° C. for 10 hours to obtain the modified hollow Prussian blue. The preparation method of the impregnation solution is: K1: By weight, 13.7 g of 2-methyl-3-mercaptofuran, 200 mL of acetonitrile, 16.6 g of allylphenylene glycol, and 3.036 g of triethylamine were stirred at 70 ° C for 60 minutes. K2: Add 1.36 g of 1-vinyl-3-methylimidazolium acetate (170) CAS: 1416358-75-2, stir at 70-80°C for 30 minutes, and cool to obtain an ionic liquid impregnation solution containing furan, phenyl sulfoxide and imidazole acetate.

[0038] D. The battery was assembled and tested, and its discharge specific capacity at a current density of 1C was 131.4 mAh / g, and the capacity retention rate after 100 cycles was 93.2%.

[0039] Embodiment 3, A method for preparing a hollow Prussian blue positive electrode material comprises the following steps: A. Synthesis of ferrous cobalt cyanide: Ferrous cobalt cyanide was prepared by the traditional bimetallic source co-precipitation method. First, 60.8 g FeSO4·7H2O and 99.7 g K3Co(CN)6·10H2O were dissolved in 120 ml deionized water, marked as solution A and solution B, respectively. Then, under argon gas protection, solution B was dropped into solution A to obtain a white precipitate. The precipitate was aged for 14 h and then collected. It was washed with deionized water and anhydrous ethanol by centrifugation for 5 times, respectively, and finally dried in a vacuum oven at 200 °C for 20 h to obtain a sample of ferrous cobalt cyanide.

[0040] B. Synthesis of hollow Prussian blue: Hollow Prussian blue was prepared by the double iron source method. First, 338.8 g Na4Fe(CN)6·10H2O was dissolved in 800 ml deionized water to form solution A. 31.8 g ferrocyanide was weighed and placed in 200 ml deionized water. Suspension B was formed by magnetic stirring. Then, under specific argon gas protection conditions, solution A was slowly dripped into solution B through a peristaltic pump. At this time, Fe(CN) in the solution 4- Fe 2+ A coprecipitation reaction occurred to form Prussian blue, and the white suspension gradually turned into a blue suspension. After the final mixed solution was placed for 36 hours, a dark blue precipitate was obtained by centrifugation, which was washed 5 times with deionized water and anhydrous ethanol respectively, and finally dried under vacuum at 0.5mTorr and 200 °C for 20 hours to obtain a hollow Prussian blue sample.

[0041] C. Soak the dehydrated hollow Prussian blue in the impregnation solution for 14 hours, filter and dry in vacuum at 80° C. for 15 hours to obtain the modified hollow Prussian blue. The preparation method of the impregnation solution is: K1: According to weight, 27.4 g of 2-methyl-3-mercaptofurofurox, 300 mL of acetonitrile, 33.2 g of allylphenyl sulfoxide, and 6.072 g of triethylamine were stirred at 80° C. for 100 minutes.

[0042] K2: Add 5.1 g of 1-vinyl-3-methylimidazolium acetate CAS: 1416358-75-2, stir at 80°C for 60 minutes, and cool to obtain an ionic liquid impregnation solution containing furan, phenyl sulfoxide and imidazole acetate.

[0043] D. The battery was assembled and tested, and its discharge specific capacity at a current density of 1C was 124.5 mAh / g, and the capacity retention rate after 100 cycles was 90.4%.

[0044] Comparative Example 1 A method for preparing a hollow Prussian blue positive electrode material comprises the following steps: A. Synthesis of ferrocyanide: ferrocyanide was prepared by the conventional double metal source coprecipitation method. First, 45.6 g FeSO4·7H2O and 66.5 g K3Co(CN)6·10H2O were dissolved in 100 ml deionized water, marked as solution A and solution B, respectively. Then, under argon gas protection, solution B was dropped into solution A. The free Fe in the solution was 2+ Will be with Co(CN) 3- The coprecipitation reaction occurred and a white precipitate was finally obtained. The precipitate was collected after aging for 12 hours, washed three times by centrifugation with deionized water and anhydrous ethanol respectively, and finally dried in a vacuum oven at 120 °C for 12 hours to obtain the sample of cobalt ferrocyanide.

[0045] B. Synthesis of hollow Prussian blue: Hollow Prussian blue was prepared by the double iron source method. First, 290g Na4Fe(CN)6·10H2O was dissolved in 500ml deionized water to form solution A. 21g ferrocyanide was weighed and placed in 100ml deionized water, and a suspension B was formed by magnetic stirring. Then, under specific argon gas protection conditions, solution A was slowly dripped into solution B through a peristaltic pump. At this time, the Fe(CN) in the solution 4- Fe 2+ A coprecipitation reaction occurred to form Prussian blue, and the white suspension gradually turned into a blue suspension. After the final mixed solution was placed for 24 hours, a dark blue precipitate was obtained by centrifugation, which was washed three times with deionized water and anhydrous ethanol respectively, and finally dried under vacuum at 0.3 mTorr and 120 °C for 12 hours to obtain a hollow Prussian blue sample.

[0046] C. The battery was assembled and tested to have a discharge capacity of 1113.5 mAh / g at a current density of 1 C. The capacity retention rate after 100 cycles was 86.4%.

Claims

1. A method for preparing a hollow Prussian blue positive electrode material, characterized in that The following steps are involved: A. Synthesis of ferrocobalt cyanide: ferrocobalt cyanide was prepared by the traditional double metal source coprecipitation method. First, FeSO4·7H2O and K3Co(CN)6·10H2O were dissolved in appropriate amounts of deionized water according to a certain molar ratio, marked as solution A and solution B. Then, solution B was dropped into solution A under argon gas protection. The free Fe in the solution 2+ Will be with Co(CN) 3- The combination undergoes a coprecipitation reaction, and finally a white precipitate is obtained. The precipitate is collected after aging, washed with a detergent, and finally dried in a vacuum oven to obtain a sample of ferrocobalt cyanide; B. Synthesis of hollow Prussian blue: Hollow Prussian blue was prepared by the double iron source method. First, an appropriate amount of Na4Fe(CN)6·10H2O was dissolved in a certain amount of deionized water to form solution A. Then, an appropriate amount of ferrous cobalt cyanide was weighed and placed in a certain amount of deionized water. Suspension B was formed by magnetic stirring. Under specific argon gas protection conditions, solution A was slowly dripped into solution B through a peristaltic pump. At this time, Fe(CN) in the solution 4- Fe 2+ A coprecipitation reaction occurs to form Prussian blue, and the white suspension gradually turns into a blue suspension. After the mixed solution is left for a period of time, it is centrifuged to obtain a dark blue precipitate, which is washed with a detergent, dried under vacuum, and dehydrated at high temperature to obtain a dehydrated hollow Prussian blue. C. Soaking the dehydrated hollow Prussian blue in the impregnation solution, filtering, and vacuum drying to obtain the modified hollow Prussian blue; E. Assemble the battery and test its discharge capacity and cycle performance at a current density of 1C.

2. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step A, the molar ratio of FeSO4·7H2O to K3Co(CN)6·10H2O is 0.2-0.4:0.1-0.

3.

3. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step A, the amount of deionized water added is 80-120 mL.

4. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step A, the precipitation aging time is 10-14 hours.

5. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step A, the detergent is one or both of deionized water and anhydrous ethanol.

6. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step A, the washing times are 2-5 times.

7. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step A, the precipitate is dried in a vacuum oven at 100-200° C. for 10-20 hours.

8. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step A, the molar ratio of Na4Fe(CN)6·10H2O to ferrous cobalt cyanide is 0.5-0.7:0.05-0.

15.

9. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step B, the amount of deionized water added to solution A is 400-800 mL, and the amount of deionized water added to solution B is 80-200 mL.

10. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step B, the suspension is placed for 12-36 hours.

11. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step B, the detergent is one or both of deionized water and anhydrous ethanol.

12. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step B, the precipitate is dried in a vacuum oven at 0.1-0.5 mTorr and 100-200° C. for 10-20 h.

13. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step C, the preparation method of the impregnation solution is: K1: According to weight, 0.12-0.24 parts of 2-methyl-3-mercaptofuran, 200-300 parts of acetonitrile, 0.1-0.2 parts of allylphenyl sulfoxide, 0.03-0.06 parts of triethylamine, stirred at 70-80°C for 60-100 minutes, K2: Add 0.008-0.03 parts of 1-vinyl-3-methylimidazolium acetate, stir at 70-80°C for 30-60 minutes, and cool to obtain an ionic liquid impregnation solution containing furan, phenyl sulfoxide and imidazole acetate.

14. The method for coating a Prussian blue positive electrode material with a conductive polymer according to claim 1, characterized in that: In step B, the dehydrated hollow Prussian blue is immersed in the impregnation solution for 8-14 hours, filtered and then vacuum dried at 70-80° C. for 10-15 hours.

Citation Information

Patent Citations

  • Method for improving crystallinity of Prussian blue, Prussian blue, positive electrode material and battery

    CN117326571A